Characterization of the galactomannans from Parkinsonia aculeata seeds and their application on affinity chromatography - Garros-Rosa,Ivone (2006)
Successive aqueous (10 ºC, 25 ºC and 80 ºC) and alkaline (1M NaOH; 25 ºC) extractions of milled Parkinsonia aculeata endosperms gave rise to four galactomannan fractions. These extractions furnished viscous galactomannans with Man:Gal ratios ranging from 3.1:1; 3.7:1; 4.9:1 and 6.1:1 (P1, P2, P3 and P4, respectively). Fraction P1 was used for structural studies by using methylation analysis, periodate oxidation and 13C-NMR. It showed a linear backbone of beta(1->4) linked D-mannose units, to which single alpha(1->6)-linked D-galactose are attached. This galactomannan has Mw 775700 g/mol and intrinsic viscosity of 558 mL/g. The four fractions and the crude endosperm were treated with epichlorydrin and used as matrix for affinity chromatography. All columns tested showed ability to bind lectin samples. The efficiency is related to the degree and pattern of substitution of galactosyl units on the D-mannan backbone.